2021
DOI: 10.1007/s10570-021-03986-5
|View full text |Cite
|
Sign up to set email alerts
|

From unavoidable food waste to advanced biomaterials: microfibrilated lignocellulose production by microwave-assisted hydrothermal treatment of cassava peel and almond hull

Abstract: Lignocellulose based nanomaterials are emerging green biosolids commonly obtained from wood pulp. Alternative feedstocks, such as as unavoidable food waste, are interesting resources for nano/microfibers. This research reports the production and characterization of microfibrillated lignocellulose (MFLC) from cassava peel (CP) and almond hull (AH) via acid-free microwave-assisted hydrothermal treatment (MHT) at different temperatures (120–220 °C). During processing, the structural changes were tracked by ATR-IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 100 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…As shown in Figure S1f, the original stacked cellulose was separated, whereas the lignin particles were still attached to the cellulose. 18 According to the above analysis, the physical and chemical synergistic pretreatment of LC can effectively disperse and dissolve its components, improve solvent accessibility between its molecular chains, and expose more adsorption active sites.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As shown in Figure S1f, the original stacked cellulose was separated, whereas the lignin particles were still attached to the cellulose. 18 According to the above analysis, the physical and chemical synergistic pretreatment of LC can effectively disperse and dissolve its components, improve solvent accessibility between its molecular chains, and expose more adsorption active sites.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Microwave-assisted hydrothermal treatment is widely used for conversion of biomass into value-added products, namely biochemicals (e.g., furfural, sugars, and carboxylic acids), biofuels, and biomaterials (e.g., hydrochars) (Table ).…”
Section: Coupling Of Hydrothermal Treatment With Other Technologiesmentioning
confidence: 99%
“…By utilizing microwave energy, this process effectively and specifically eliminates hemicellulose, pectin, and amorphous cellulose from the biomass. This approach has been successfully applied to various biomass sources for production of pectineus and cellulosic materials [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been found that cellulose recovered from MW extraction may lead to the formation of hydrogels. Several studies demonstrate that water and cellulose exhibit a strong affinity, allowing them to form gels [ 10 , 12 , 13 , 14 , 15 ]. The abundant hydroxyl groups present in cellulose play a vital role in creating a three-dimensional hydrogel by attracting and retaining water through hydrogen bonding [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation